AN ANALYSIS OF THIRD SEMESTER STUDENTS’ READING INTEREST TOWARDS ACADEMIC ACHIEVEMENT AT THE UNIVERSITY OF ISLAM MALANG - ayudya nurhaliza zuhro (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading is the most fundamental skill in term of acquiring information, it allows the reader to obtain knowledge from any parts of the world. Nowadays reading material can be easily obtained through internet, this quick access to information should be able to develop students’ reading interest. Developing reading interest allows the reader to be more literate and improves analytical skill in comprehending text as well as to collect information and academic achievements. Therefore, the researcher interested to study, students’ reading interest in academic purposes. This study was conducted using descriptive qualitative research design to find out the students’ interest in reading related to their academic importance. The participants in this study is 31 students from third semester students at University of Islam Malang and 10 of them were selected for the interview. The questionnaire was analyzed using excel and the interview was analyzed using descriptive qualitative query analysis that consist of data reduction, data management, interpretation and drawing conclusion. The result shows that students’ interest to read, comes from many factors including enjoyment, willingness, consciousness and attention. Moreover, there are many difficulties encountered by the students including boredom, laziness, lack of option and too difficult reading materials as most of the students tend to choose their own reading materials. The result of the study offers solution to improve reading interest such as start reading, finding interesting material that suit their interest instead of just reading learning materials, and motivate themselves to read a lot so eventually reading might become their habit.Key Words: Reading interest, academic purposes.